Phase transitions and hard magnetic properties for rapidly solidified MnAl alloys doped with C, B, and rare earth elements - Liu, Z. W. (2013)
MnAl alloys are attractive candidates to potentially replace rare earth hard magnets because of their superior mechanical strength, reasonable magnetic properties, and low cost. In this study, the phase transitions and magnetic properties of melt spun Mn55Al45 based alloys doped with C, B, and rare earth (RE) elements were investigated. As-spun Mn–Al, Mn–Al–C, and Mn–Al–C–RE ribbons possessed a hexagonal ε crystal structure. Phase transformations between the ε and the L10 (τ) phase are of interest. The ε → τ transformation occurred at ~500 °C and the reversed τ → ε transformation was observed at ~800 °C. Moderate carbon addition promoted the formation of the desired hard magnetic L10 τ-phase and improved the hard magnetic properties. The Curie temperature T C of the τ phase is very sensitive to the C concentration. Dy or Pr doping in MnAlC alloy had no significant effect on T C. Pr addition can slightly improve the magnetic properties of MnAlC alloy, especially JS. Doping B could not enhance the magnetic properties of MnAl alloy since B is not able to stabilize either the ε phase or the L10 hard magnetic τ phase.